2003
DOI: 10.5194/hess-7-937-2003
|View full text |Cite
|
Sign up to set email alerts
|

Microwave radiometric measurements of soil moisture in Italy

Abstract: Within the framework of the MAP and RAPHAEL projects, airborne experimental campaigns were carried out by the IFAC group in 1999 and 2000, using a multifrequency microwave radiometer at L, C and X bands (1.4, 6.8 and 10 GHz). The aim of the experiments was to collect soil moisture and vegetation biomass information on agricultural areas to give reliable inputs to the hydrological models. It is well known that microwave emission from soil, mainly at L-band (1.4 GHz), is very well correlated to its moisture cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…During the SOP, soil moisture was sampled on a continuous time basis at five sites with time domain 873 reflectometer (TDR) probes and at nine sites during the four missions of a helicopter-borne microwave radiometer in the C, X and L bands and different polarizations. Macelloni et al (2003) showed how the sensitivity of the radiometer to different surface types and roughness confirmed previous literature data (Wang et al, 1983), although electromagnetic interference prevented a completely successful use of the microwave antennae for soil moisture monitoring in the investigated area. The recent literature also confirms that active microwave sensors, although promising, are still far from being effective for soil moisture monitoring in mountain areas because the effect of surface roughness, vegetation and topography overcomes the influence of soil moisture on the backscattered signal.…”
Section: Field Measurementssupporting
confidence: 73%
“…During the SOP, soil moisture was sampled on a continuous time basis at five sites with time domain 873 reflectometer (TDR) probes and at nine sites during the four missions of a helicopter-borne microwave radiometer in the C, X and L bands and different polarizations. Macelloni et al (2003) showed how the sensitivity of the radiometer to different surface types and roughness confirmed previous literature data (Wang et al, 1983), although electromagnetic interference prevented a completely successful use of the microwave antennae for soil moisture monitoring in the investigated area. The recent literature also confirms that active microwave sensors, although promising, are still far from being effective for soil moisture monitoring in mountain areas because the effect of surface roughness, vegetation and topography overcomes the influence of soil moisture on the backscattered signal.…”
Section: Field Measurementssupporting
confidence: 73%
“…Indeed, modeling techniques are very important for supporting data interpretation and for addressing the many unresolved issues that still limit applications of SWC measurement at this scale (such as down-and upscaling techniques and analysis of spatial heterogeneities). Determination of SWC from airplanes and helicopters using microwave remote sensing was presented by Macelloni et al (2002Macelloni et al ( , 2003, with scattering coefficients used to determine soil moisture. Santi et al (2009) presented a study where an airborne campaign with multifrequency microwave radiometers at L, C, and X bands was carried out on a flat alluvial area in northern Italy, in the Po Valley, with the aim of improving the estimation of airborne soil moisture and vegetation biomass maps, using both active and passive sensors.…”
Section: Water Content Measurement At Different Spatial Scalesmentioning
confidence: 99%
“…The Toce basin was a case study of the RAPHAEL (Runoff and atmospheric processes for flood hazard forecasting and control) European Union research project, whose objective was to improve flood forecasting in complex mountain watershed Ranzi, 2000, 2003;Montaldo et al, 2002Montaldo et al, , 2004Bach et al, 2003;Grossi and Falappi, 2003;Macelloni et al, 2003;Richard et al, 2003). Montaldo et al (2002Montaldo et al ( , 2004 demonstrated that the FEST98 model cited above is able to simulate adequately three recent flood events in the Toce basin (in 1993, 1994 and 1997).…”
Section: Introductionmentioning
confidence: 99%